Delayed Citrus Stimulation and Prevention of Salivary Glands Damage in Patients of Thyroid Carcinoma Treated by Radioiodine Therapy - Reza, Sharmin; Sultana, Sadia; Begum, Fatima; Perveen, Rahima; Jabin, Zeenat; Nahar, Nurun; Alam, Faridul (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: It is well established that citrus stimulation has a definite role in preventing salivary gland damage after radioiodine therapy. The aim of this study was to observe how effectively this stimulation can be used to prevent salivary gland damage and whether the timing of sucking citrus substances play any role in preventing this damage more effectively. Patients and Methods: A total of 128 differentiated thyroid cancer (DTC) patients who received radioiodine treatment for thyroid carcinoma were divided into two groups- group-A and group-B. Group-A patients started citrus stimulation 1 hour after radioiodine ingestion and group-B patients started 24 hours after RAIT. Patients were followed-up at 5th day, 3rd month, and 6th month after RAIT. Follow up procedure consisted of physical examination and history of pain and swelling in salivary gland regions, taste dysfunction and dryness of mouth. Result: The incidence of different types of salivary glands side effects and abnormal scan findings were significantly high in the group of patients who were advised to start citrus stimulation 1 h after radioiodine ingestion. On the other hand, patients who started citrus stimulation 24 h after RAIT suffered less from salivary gland side effects. Conclusion: This study showed that delayed initiation of citrus stimulation was more effective in reducing salivary gland damage after RAIT. Bangladesh J. Nuclear Med. 21(2): 92-96, July 2018